Cardinal Enea Silvio Piccolomini and the Development of Cardinal Protectors of Nations - Cotta-Schönberg, Michael von (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2015)
This article deals with the development of Cardinal Protectors of Nations in the 15th century. It is based partly on texts examined by Josef Wodka (1938), partly on the correspondence of Cardinal Enea Silvio Piccolomini published in the Opera Omnia edition of 1571 and the correpondence of King Christian 1. with the Papal Court. The author’s interpretation of the development differs somewhat from Josef Wodka’s in that it recognizes the decisive role of the Council of Basle in creating a legal base for cardinals representing royal interests at the Apostolic Sea. The Council agreed with the stance of Pope Martin V that cardinals should act as impartial and independent advisors of popes, but – reaching back to Avignonese precedents – it accepted a form of representation termed “promotorship” rather than “protectorship” of royal affairs. It did not indicate any difference of content between the two concepts, but only addressed the modalities of partiality and payment. This interpretation is based on the Conciliar Decree itself and on the Cardinal’s correspondence which documents the practice at the Papal Court in the 1450’s, including a formal arrangement of promotorship between the Cardinal and the Emperor, and negotiations concerning such a promotorship between the Cardinal and the King of Denmark.